Track-Two Diplomacy: A Case of Jirga in Pakistan-Afghanistan Relations - Farhan, Muhammad; Hashmi, Rehana Saeed (Annals of Human and Social Sciences, 2023)
Track-two diplomacy, an informal and non-governmental approach to support official diplomatic efforts, is pivotal in resolving conflicts and fostering peace. This paper delves into the specific case of Jirga, a prominent informal institution in Pashtun society, to examine its function as a track-two diplomatic tool for fostering communication, building trust, and advancing peace between Pakistan and Afghanistan. Using qualitative research, it emphasizes Jirga's unique traits like community involvement and consensus-building, highlighting its role in promoting dialogue and peace at local and global levels. The study reveals Jirga's potential to complement formal diplomacy by providing an alternative platform for constructive discussions on persistent issues. Jirga also influences public opinion towards resolving challenges like Afghan refugee repatriation, the Durand Line, and cross-border terrorism. It stresses the need to integrate Jirga principles into formal peace processes, leveraging its cultural significance for a more inclusive and lasting peace between the two nations.